Integrating Sustainable Development Goals (SDGs) into Human Resource Management: A Systematic Review, Critical Appraisal, and Framework for the Logistics and Transportation Sector - Darwisman, Samuel; Simanjuntak, Yosef Ricky; Sihombing, Sarinah; Setyawati, Aswanti (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The logistics and transportation sector faces pressure to align with the Sustainable Development Goals (SDGs), yet the role of Human Resource Management (HRM) lacks a synthesized, critically appraised evidence base. This study closes this gap via a systematic literature review guided by PRISMA 2020. Searching major databases yielded 25 high-impact review articles (2019-2025), which were critically appraised using the CASP checklist. Thematic analysis identified five core determinants for successful integration: Technological Adoption, Circular Economy Principles, Coherent Policy Frameworks, Workforce Awareness, and Sustainable Resource Management. Based on these findings, we propose an integrative socio-technical framework. This study provides a validated, evidence-based roadmap for stakeholders to develop resilient and sustainable HRM strategies, moving beyond a simple literature summary to offer a critically validated foundation for the industry.